2016
DOI: 10.1177/1078155215607089
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of pharmacist interventions in an ambulatory palliative care practice

Abstract: A pharmacist-led outpatient palliative care practice identified medication problems for management of pain, constipation, and nausea/vomiting. Medication changes involved a change in dose and/or initiating a new medication. Trends were observed in improvement and stabilization of pain over subsequent clinic visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 37 publications
3
46
0
2
Order By: Relevance
“…After reviewing the titles and abstracts, 617 records were excluded because they did not include a study of pharmacist interventions in adult patients with cancer; did not assess the impact of interventions; or included non‐ambulatory patients. The remaining 40 records were selected for full‐text examination, of which 11 met all the eligibility criteria and were included in this systematic review . The excluded studies and the reasons for their exclusion are detailed in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the titles and abstracts, 617 records were excluded because they did not include a study of pharmacist interventions in adult patients with cancer; did not assess the impact of interventions; or included non‐ambulatory patients. The remaining 40 records were selected for full‐text examination, of which 11 met all the eligibility criteria and were included in this systematic review . The excluded studies and the reasons for their exclusion are detailed in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in English and reported between 2012 and 2016. Sample size ranged from 12 to 249 individuals, with most studies including sample sizes smaller than 100 individuals (n=7) . In most studies (n=10), the mean age of patients was >50 years, and an equal proportion of men and women was recruited.…”
Section: Resultsmentioning
confidence: 99%
“…16,22,23 Wilson et al 23 reported that implementation of pharmacist recommendations in a palliative care setting was 1 of the strongest predictors of patients achieving desired outcomes. Because the purpose of this study was to evaluate the impact of a previsit pharmacist review, and in an attempt to evaluate an intervention that could feasibly be added to other current pharmacist clinic responsibilities, the pharmacists did not implement any of the intervention recommendations but rather deferred implementation to the prescriber.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature on pharmacist engagement in chronic pain management is limited to specialty care settings (eg, palliative care), investigations of patient-centered medical home designation, or descriptive reports. 15,16,[22][23][24][25] To our knowledge, this is the first published study of the impact of a pharmacist-led intervention focused on comprehensive chronic pain management in a family medicine setting. The purpose of this study was to evaluate the impact of a previsit pharmacist review of highrisk patients treated with opioids for chronic noncancer pain for compliance with CDC recommendations at a family medicine residency clinic.…”
mentioning
confidence: 99%
See 1 more Smart Citation